The relatively young, metal-poor and distant open cluster NGC 2324 - Piatti, Andres Eduardo (2004)
We have obtained CCD photometry in the Johnson V, Kron-Cousins I and CT1 Washington systems for NGC 2324, a rich open cluster located ∼35◦ from the Galactic anticentre direction. We measured V magnitudes and V − I colours for 2865 stars and T1 magnitudes and C − T1 colours for 1815 stars in an area of 13. 6 × 13. 6. The comparison of the cluster colour–magnitude diagrams with isochrones of the Geneva group yield E(V − I) = 0.33 ± 0.07 and V − MV = 13.70 ± 0.15 for log t = 8.65 (t = 440 Myr) and Z = 0.008 ([Fe/H] = −0.40), and E(C − T1) = 0.40 ± 0.10 and T1 − MT1 = 13.65 ± 0.15 for the same age and metallicity level. The resulting E(V − I) reddening value implies E(B − V) = 0.25 ± 0.05 and a istance from the Sun of (3.8 ± 0.5) kpc. Star counts carried out within and outside the cluster region allowed us to estimate the cluster angular radius as 5. 3 ± 0. 3 (5.9 pc). When using the E(B − V) reddening value here derived and the original Washington photometric data of Geisler et al. (1991) for the stars confirmed as red cluster giants from Coravel radial velocities, we found [Fe/H] = −0.31 ± 0.04, which is in good agreement with the best fits of isochrones. Therefore, NGC 2324 is found to be a relatively young, metal-poor and distant open cluster located beyond the Perseus spiral arm. A comparison of NGC 2324 with 10 well-known open clusters of nearly the same age shows that the cluster metal abundance and its position in the Galaxy are consistent with the existence of a radial abundance gradient of −0.07 dex kpc−1 in the Galactic disc.